Authority of the Environmental Service in Disaster Management Based on the Law on Environmental Protection and Management - Suwari Akhmaddhian; Haris Budiman; Erga Yuhandra; Dikha Anugrah; Frisca Meilan Dwi Lestary; Wina Puspasari; Teti Mardiani (Universitas Kuningan, 2022)
The environment can be a resource or even a hazard when a disaster occurs. Natural disasters as natural phenomena that can occur at any time regardless of day or night with the risk of loss of property to the psyche must be anticipated with disaster management activities in accordance with the Disaster Law in Indonesia. The purpose of this research is to find out and analyze the regulations made by the government in efforts to deal with disasters in Indonesia, especially in Kuningan Regency. The method used in this study is an empirical juridical approach using primary data and secondary data as well as data collection tools used in the form of interviews, observation and literature studies. The results of this study are the implementation of work programs and activities from the Department of the Environment in disaster management based on Law Number 24 of 2007 concerning Disaster Management. The conclusion of this writing is that the arrangements related to disaster management are adequate from the central to the regional level with the Implementation of the Environmental Service in the basic efforts of disaster management that have been carried out but must be further improved. Suggestions for implementing the implementation of the Environmental Service are to cooperate with students to carry out counseling and outreach about environmental preservation in disaster management efforts based on the Disaster Law in Kuningan Regency.